A case-referent study on acute myeloid leukemia, background radiation and exposure to solvents and other agents - Flodin, Ulf; Andersson, Lennart; Anjou, Carl-Göran; Palm, Ulla-Britt; Vikrot, Olle; Axelson, Olav (Scandinavian Journal of Work, Environment & Health, 1981)
The effect of potential risk factors for acute myeloid leukemia was evaluated in a case-referent study encompassing 42 cases and 244 referents, all deceased. Information on exposure was obtained with questionnaires mailed to the next of kin. Particularly the effect of background radiation was evaluated, as assessed with a gamma radiation index weighing the time spent outdoors and indoors and considering the building material (stone, wood, etc) in the homes and the workplaces of the subjects. Especially between the ages of 20 and 49 a, to some extent also between 50 and 69 a but not above 70, there seemed to be an effect from background radiation and a trend suggesting an exposureeffect relationship. There was also about a sixfold increase in the rate ratio with regard to solvent exposure, which also seemed to modify the effect of background radiation. Other exposures were associated with relatively modest increases in the rate ratios and/or very small numbers of exposed individuals. It would be worthwhile to undertake further cancer epidemiologic studies of background radiation in which effective study designs are applied and a variety of potential confounders and modifiers of effect are identified and accounted for.
Keywords: acute myeloid leukemia; agent; animal contact; background radiation; case-control design; case-referent design; case-referent study; exposure; gamma radiation; leukemia; lowdose radiation; pesticide exposure; radiation; solvent; solvent exposure; X-ray exposure